Multi-objective Supply Restoration in Active Distribution Networks with Soft Open Points - Li, Zhicheng; Tang, Zhijun; Chao, Wujie; Zou, Huanxiong; Wu, Xiangyu; Lin, Chenxiang (2018 2nd IEEE Conference on Energy Internet and Energy System Integration (EI2), 2018)
The flexible interconnection technology based on soft open points (SOPs) provides opportunities to improve the operating level of active distribution networks (ADNs). The capability to achieve fast supply restoration is one of the important advantages of SOPs. This paper proposes a hybrid bi-level optimization method for multi-objective supply restoration in the ADNs with SOPs. The model of supply restoration for minimizing the out-of-service loads, the number of switch operations, and the network losses, is established. The model is formulated as a typical mixed integer nonlinear programming (MINLP) problem, taking the power outputs of SOPs and switch states as controllable variables. The optimization method based on fast non-dominated sorting genetic algorithm (NSGA-II) and primal-dual interior-point method (PDIPM) is developed to solve it. NSGA-II is employed to reconfigure the switch states. For the network topology reconfigured by NSGA-II, an AC/DC OPF based on PDIPM is conducted to obtain the minimum power losses and to ensure the system operation constraints satisfied. A modified IEEE 33-node test system is carried out to demonstrate the effectiveness of this method. Results show that the application of SOPs effectively reduces the healthy out-of-service loads, and simplifies the switching operations required.